Impact of Clinical Predictors and Routine Coronary Artery Disease Testing on Outcome of Patients Admitted to Chest Pain Decision Unit. Issue 3 (19th November 2013) - Cotarlan, Vlad; Ho, David; Pineda, John; Qureshi, Anwer; Shirani, Jamshid
Abstract Background Chest pain decision unit (CDU) evaluation of patients with acute chest pain (ACP) and nondiagnostic electrocardiogram (ECG) usually includes noninvasive testing for coronary artery disease (CAD). Hypothesis CAD evaluation will not improve clinical outcome in low‐risk ACP patients. Methods We studied 459 adults admitted to CDU with ACP and no troponin release who underwent noninvasive CAD testing (stress testing in 396 and coronary computed tomographic angiography in 63). Multivariate logistic regression was used to determine predictors of adverse outcome over a 3‐year follow‐up period. Results Initial noninvasive test was normal in 367 (80%) and abnormal (positive or indeterminate) in 92 (20%). A total of 42 (9%) patients underwent invasive coronary angiography, and 16 (3.5%) underwent revascularization. During follow‐up, 33 patients had a total of 36 major clinical events: 12 revascularizations, 9 myocardial infarctions, and 15 deaths. Multivariate logistic regression analysis identified abnormal ECG (odds ratio [OR]: 2.7, P = 0.03), typical chest pain (OR: 3.8, P = 0.002), diabetes (OR: 4.1, P = 0.001), and known CAD (OR: 2.3, P = 0.03) as independent predictors for adverse outcome, but not noninvasive test result. Thus, in 187 patients with no high‐risk features (41% of the cohort), the annualized event rate was 0.5%. In 272 patients with at least 1 high‐risk feature, annualized event rates were 2.8% and 5.7% when noninvasive test was normal or abnormal, respectively (P = 0.04). Conclusions Clinical risk stratification allows identification of patients at low risk of adverse outcome over an intermediate period of follow‐up. Noninvasive testing is not warranted in such patients.